Use of double mass curves in hydrologic benefit evaluations - Gao, Peng; Li, Pengfei; Zhao, Baili; Xu, Ruirui; Zhao, Guangju; Sun, Wenyi; Mu, Xingmin (Hydrological processes, 2017)
Environmental change resulting from intensified human interventions and climate change has impacted the hydrological function of many large river systems, largely altering the production and transport of run‐off and sediment. It is thus vital to quantitatively evaluate the influence of climate change and human activities on streamflow and sediment discharge. Water balance equations, hydrological models, and comparative analyses are commonly used to fulfil this need. Double mass curves (DMCs), being one useful method for comparative analyses, are characterized by low data requirements and high transferability, and thus more practical than water balance equations and hydrological models for hydrologic benefit evaluations. However, the detailed derivation procedure of the DMC has, to date, yet been described in literature. Moreover, in previous studies, changing points of the DMC were determined either rather empirically or as the changing point of streamflow or sediment discharge (i.e., precipitation was not considered). Hence, the changing point detected may be subject to inaccuracies. This paper, for the first time, comprehensively detailed the derivation procedure of the DMC; a new way was proposed to quantitatively examine the changing point of the DMC; an example was also given to demonstrate the use of the DMC in the hydrologic benefit evaluation. It is hopeful that the method given in our paper will be widely adopted by future studies as a standard procedure to derive and use the DMC.